2011
DOI: 10.1128/jcm.00952-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chlamydia trachomatis and Neisseria gonorrhoeae Detection in Urine, Endocervical, and Vaginal Specimens by a Multiplexed Isothermal Thermophilic Helicase-Dependent Amplification (tHDA) Assay

Abstract: We have developed a new research assay that combines sequence-specific sample preparation and isothermal amplification for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae infections. The assay targets both the omp gene and the cryptic plasmid of C. trachomatis and the multicopy opa gene of N. gonorrhoeae, which are amplified and detected in a single reaction. We evaluated the ability of the assay to detect C. trachomatis and N. gonorrhoeae infections in first-catch urine, swab, and liquid-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We have identified 11 published papers where there are comparisons between vulvovaginal swabs and endocervical swabs using nucleic acid amplification tests for the detection of chlamydia 79 10 11 13 14 15 16 17 18 19 One included a comparison using two different nucleic acid amplification tests, making 12 comparisons in total 19. Two of the comparisons found a higher sensitivity with the endocervical swabs, with differences of 1.8%15 and 0.6%,11 whereas 10 found a higher sensitivity with the vulvovaginal swabs, with a median of 5.1% difference and a range of 1.2–16.0% 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified 11 published papers where there are comparisons between vulvovaginal swabs and endocervical swabs using nucleic acid amplification tests for the detection of chlamydia 79 10 11 13 14 15 16 17 18 19 One included a comparison using two different nucleic acid amplification tests, making 12 comparisons in total 19. Two of the comparisons found a higher sensitivity with the endocervical swabs, with differences of 1.8%15 and 0.6%,11 whereas 10 found a higher sensitivity with the vulvovaginal swabs, with a median of 5.1% difference and a range of 1.2–16.0% 7…”
Section: Discussionmentioning
confidence: 99%
“…On transferring to the Aptima Combo-2 assay, we needed to choose between endocervical and vulvovaginal sampling. Most studies have shown that the two samples are equivalent,4 7 10 13 14 15 16 17 18 19 suggesting that, when a woman is undergoing an examination, an endocervical swab would be preferable on the assumption that it is superior for detecting low chlamydial load in the endocervix (which if missed could leave women at risk of ascending infection). However, one study found vulvovaginal swabs to be significantly more sensitive than endocervical swabs (81% v 65%), although the authors commented that the sensitivity of the endocervical swabs was lower than in previously published studies 9.…”
Section: Introductionmentioning
confidence: 99%
“…38 Among the targets used to identify C. trachomatis, a cryptic plasmid has been the most widely used for NAATs. [39][40][41] However, it was subsequently shown that sequence variation of cryptic plasmids has been detected in several countries. [42][43][44] This demonstrates that false-negative results may occur when a cryptic plasmid is used alone as the target for detection of C. trachomatis particularly when screening clinical samples from this region.…”
Section: Discussionmentioning
confidence: 99%
“…There is no need for an initial denaturation step for DNA and the reaction has the ability to detect RNA [108][109][110][111]. HDA has been shown to be effective for various samples, from urine [112] and vaginal swabs [112] to blood [110,111] and stool [108,109]. Therefore, the HDA has a great potential for using it in portable pointof-care devices [113].…”
Section: E Colimentioning
confidence: 99%